PERLINDUNGAN HUKUM TERHADAP KARYAWAN YANG BEKERJA SHIFT MALAM (STUDI PADA PT INDOMARCO PRISMATAMA) - Faisal, Muhamad; Arman, Zuhdi (LPPM Universitas Putera Batam, 2020)
HumankResources (HR) is thehmost importantyasset in akcompany. Employeeshcan be a goodhpotential if managedhproperly andhcorrectly, butkemployees canjalso become a burden if thekcompany cannot managekthem well. Along with the increase in the business world, especially companieshengaged in retail in the city of Batam, which has become negative in the eyes of the public related to work safety, workplace accidents, occupational diseases, This study is entitled